2015
DOI: 10.1152/ajpgi.00133.2015
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory effect and potential mechanism of cardamonin in DSS-induced colitis

Abstract: Cardamonin is a naturally occurring chalcone with strong anti-inflammatory activity. However, the direct effect of cardamonin on intestinal inflammation remains elusive. In the present study, we found that cardamonin markedly ameliorated dextran sulfate sodium-induced mouse body weight loss, diarrhea, colon shortening, spleen swelling, and histological damage, which correlated with a decline in the activity of myeloperoxidase and the production of nitric oxide, tumor necrosis factor-α and interleukin-6 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 28 publications
2
40
1
Order By: Relevance
“…26 Moreover, extensive research has shown that increased proinflammatory cytokines and chemokines were associated with IBD. 27 Result of the present study showed that PCSK9 inhibition effectively decreased the secretion of TNF-α, IL-1β, IL-6, MCP-1, and ICAM-1 in the colon of TNBS-induced colitis rats, suggesting anti-inflammation role against IBD.…”
Section: Discussionsupporting
confidence: 54%
“…26 Moreover, extensive research has shown that increased proinflammatory cytokines and chemokines were associated with IBD. 27 Result of the present study showed that PCSK9 inhibition effectively decreased the secretion of TNF-α, IL-1β, IL-6, MCP-1, and ICAM-1 in the colon of TNBS-induced colitis rats, suggesting anti-inflammation role against IBD.…”
Section: Discussionsupporting
confidence: 54%
“…In this study, cardamonin and rapamycin inhibited the expression of TNF-α and IL-6 under both conditions. This finding is consistent with those of previous studies wherein cardamonin has been reported to exhibit anti-inflammatory effects [40]. Further studies have demonstrated that cardamonin inhibits inflammation through p65NF-kappaB inhibition in LPS-stimulated RAW 264.7 macrophages and BV2 microglia [20,41].…”
Section: Discussionsupporting
confidence: 93%
“…The increased MPO levels were significantly reduced after the administration of genistein and quercitrin in the TNBS model [ 61 , 68 ]. A similar effect was induced by quercitrin as well as with cardamonin, chrysin, EGCG, naringenin and rutin in the DSS model [ 40 , 50 , 55 , 56 , 57 , 60 , 69 ]. Finally, it is important to remark that rutin administration was also able to reduce leukocyte infiltration in the T cell transfer model [ 70 ].…”
Section: Intestinal Anti-inflammatory Effects Of Flavonoids: mentioning
confidence: 64%
“…In the DSS model, characterized by intense colonic damage associated with inflammatory cell infiltration and epithelial crypt loss, which results in acute clinical symptoms including body weight loss, bloody stools and diarrhea, the treatment with some flavonoids such as cardamonin, chrysin, naringenin, EGCG, glabridin, rutin and quercitrin significantly reduced the Disease Activity Index (DAI), which is used to monitor the severity of the inflammatory process, as well as the colon shortening. Therefore, DSS-induced weight loss and histological damage were significantly ameliorated by flavonoid treatment [ 40 , 50 , 55 , 56 , 57 , 58 , 59 , 60 ]. In line with this finding, it has been shown that quercitrin and rutin administration was able to decrease colonic damage, reducing the length of the injury and attenuating the diarrhea symptoms in the TNBS model [ 61 , 62 ].…”
Section: Intestinal Anti-inflammatory Effects Of Flavonoids: mentioning
confidence: 99%